2022
DOI: 10.1177/11795549221086578
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Post First-Line Chemotherapy Glasgow Prognostic Score in Advanced Non-Small Cell Lung Cancer

Abstract: Background: The Glasgow prognostic score (GPS) is an established inflammatory prognostic index in cancer patients. Most studies have only measured GPS at baseline (B-GPS). Effective cancer therapy may reduce inflammation, and we investigated whether re-assessing GPS after first-line chemotherapy (E-GPS) provided more prognostic information than B-GPS in a phase III trial of advanced non-squamous non-small cell lung cancer (NSCLC). Methods: Glasgow prognostic score was assessed before and after carboplatin/vino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
1
1
0
Order By: Relevance
“…Furthermore, it successfully passed cross-validation for internal validity and is announced for assessment in subsequent research. That CRP measurements during therapy can reveal additional information above the baseline value has been also shown by some other studies on immunotherapy in advanced NSCLC 58 61 .…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, it successfully passed cross-validation for internal validity and is announced for assessment in subsequent research. That CRP measurements during therapy can reveal additional information above the baseline value has been also shown by some other studies on immunotherapy in advanced NSCLC 58 61 .…”
Section: Discussionsupporting
confidence: 66%
“…Some of these studies were conducted in patients who underwent surgery in the early stage [ 21 ], and some in advanced patients [ 22 ]. In many studies, mGPS was generally examined before treatment, but there are also studies investigating the efficacy of treatment with mGPS after treatment [ 23 , 24 ]. It has been shown that mGPS has a positive effect on survival for patients who receive radiation therapy [ 25 ].…”
Section: Discussionmentioning
confidence: 99%